Symposium on EC Structural Funds - Barrett, Sean D. (Statistical and Social Inquiry Society of Ireland, 1993)
Ireland is the recipient of one of the largest foreign aid programmes in the world. Our net receipts from the EC between 1990 and 1992 averaged 6.7 per cent of GNP. The EC has three structural funds; the guidance section of FEOGA (the Agricultural Fund), the Social Fund and the Regional Fund; a fourth, the Cohesion Fund, is to come into effect before the end of 1993 under the Maastricht Treaty. The share of structural spending in the EC budget is set to increase from 18 per cent in 1987, to 29 per cent in 1992 and 36 per cent in 1999.
EC structural funds
Read before the Society, 4 March 1993
Keywords: European funds; Transportation infrastructure; 314.15